PENGARUH JENJANG PENDIDIKAN, LATAR BELAKANG PENDIDIKAN, SKALA USAHA DAN UMUR USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA PELAKU UMKM DI KECAMATAN BOYOLALI - Ummah, Fitri Khoiru; Kristianto, Djoko; Sunarti, Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to analyze the effect of education level, educationalbackground, business scale and business age on the use of accountin information forUMKM actors in Boyolali sub-district. The type of data used is quantitative data. Thedata source used is primary data. The sampling technique was carried out usingrandom sampling methods. The sample used was 93 respondents to owner/managerof the UMKM. How to collect data by distributing questionnaires to UMKM businessowner in Boyolali sub-district. Based on the test result from the research, it isconcluded that the level of education has a significant effect on the used ofaccounting information, educational background has a signifivant effect on the use ofaccounting information, business scale has a significant effect on the use ofaccounting information and business age has a significant effect on the use ofaccounting information for UMKM actors in Boyolali sub-district.